KESIAPAN PEMERINTAH KELURAHAN PETARUKAN KECAMATAN PETARUKAN KABUPATEN PEMALANG PROVINSI JAWA TENGAH DALAM PENGELOLAAN DANA KELURAHAN - Tumija Tumija (Jurnal Media Birokrasi, 2021)
This study aims to obtain an overview of the readiness of the Petarukan sub-district government, Petarukan District, Pemalang Regency in managing village funds. The method used in this research is descriptive with an inductive approach. Data collection techniques by interview, documentation, namely data reduction, data presentation, and conclusions. The result of the research is that the Petarukan Village government is ready to manage the Village Fund. It can be seen from the four dimensions that the authors analyze in this study, namely the first dimension of organizational readiness, that the sub-district government has proposed a village fund management structure consisting of the lurah as the Budget User Authority (KPA), the Secretary of the Lurah as the Commitment Making Officer (PPK). ) and each Section Head as Activity Technical Making Officer (PPTK) and Assistant Treasurer. Second, the dimension of the system, in the activities of inputting or entering data already using an application, namely SIMPDA. Third, the dimensions of human resources, human resources that support the management of the Village Fund are sufficient in terms of numbers but not all of them are included in training or workshops to increase competence. Fourth, the dimensions of facilities and infrastructure, in Petarukan Village the existing facilities and infrastructure are in relatively good condition and ready to support the management of the Village Fund. Keywords: Readiness, Management, Village Fund